Increasing Senior High School Students’ Ability In Speaking English Through Contextual Storytelling Method - Meyke Machrita Mamahit (Universitas Negeri Makassar, 2017)
This research aimed (1) to increase the ability of students XII Grade Science 6 Senior High School state 7 Manado in speaking English through contextual storytelling method, (2) to increase the motivation and interest of students XII Grade Science 6 Senior High School state 7 Manado in speaking English through contextual storytelling method. This research is Classroom Action Research. The population was 325 students and the sample was 30 students. The research data was collected using performance test of cycle 1, 2, 3 and questionnaire. The research results indicated that the use of contextual storytelling method in learning English significantly increased the ability, interest and motivation of students XII Grade Science 6 Senior High School state 7 Manado in speaking English. The percentage of students who achieved the minimum score increased from 60 % in the first cycle became 70 % in the second cycle, and it increased 90 % in the third cycle. The students’ interest and motivation in speaking English increased from 70 % in first cycle became 80 % in the second cycle and it became 90 % in the third cycle.